Pengembangan Lembar Kerja Peserta Didik Pada Pembelajaran Tematik Subtema Pentingnya Udara Bersih Bagi Pernapasan Kelas V - Farisa Irwayu; Hery Hery Kresnadi; Asmayani Salimi; Kartono Kartono; Siti Halidjah (Journal on Education, 2023)
The purpose of this study was to produce student worksheets in accordance with the needs of students in understanding the material presented in thematic learning. This study aims to identify the feasibility of student worksheet products with the method used, namely the ADDIE method with the stages of Analysis, Design, Development, Implementation, and Evaluation. The feasibility of this product is assessed from the aspects of content, design and language. The data source for this research was 30 students in class V A of Elementary School 26 Pontianak Tenggara, totaling 30 people with two stages of research implementation. The difference in assessment at the two stages of the research is that students like questions or assignments that vary with illustrated pictures that attract attention so that it makes it easier to understand the material for each subject contained in each learning that takes place. Thus the use of illustrated pictures and varied forms of questions can attract students' interest in learning along with the subject matter of learning in each activity on the worksheet helping students understand the material presented by the teacher.